Penerapan Model Pembelajaran SQ3R Berbantuan Cerita Bergambar Untuk Meningkatkan Kemampuan Menulis Teks Narasi Kelas IV SD GMIT No.7 Oebufu Kupang - Benyamitra Pandie, Risnyati; Robot, Marselus; Sampe, Markus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low narrative writing skills of fourth-grade students at SD GMIT No. 7 Oebufu Kupang. Based on preliminary observations, students experienced difficulties in developing ideas, organizing story sequences coherently, selecting appropriate vocabulary, and applying correct spelling and punctuation according to Indonesian language rules. In addition, the learning process was still teacher-centered and had not utilized learning models and media that could enhance students' active participation in writing activities. This study aimed to improve students' narrative writing skills through the implementation of the Survey, Question, Read, Recite, and Review (SQ3R) learning model assisted by picture stories. This research employed Classroom Action Research (CAR), which was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection stages. The participants of this study were 25 fourth-grade students of SD GMIT No. 7 Oebufu Kupang. Data were collected through tests, observations, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the implementation of the SQ3R learning model assisted by picture stories successfully improved students' narrative writing skills. This improvement was indicated by the increase in students' average scores from 42 in the pre-cycle stage with a classical mastery level of 16%, to 66 in Cycle I with a mastery level of 44%, and further to 86 in Cycle II with a mastery level of 96%. Furthermore, teacher activity increased from 64% to 92%, while student activity improved from 57 to 88. Therefore, the SQ3R learning model assisted by picture stories was proven to be effective in improving the narrative writing skills of elementary school students.